2003
DOI: 10.1038/sj.npp.1300265
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotine on Leading Saccades during Smooth Pursuit Eye Movements in Smokers and Nonsmokers with Schizophrenia

Abstract: Several studies have shown that schizophrenic patients and their biological relatives generate a greater number of leading saccades during smooth pursuit eye movement (SPEM) tasks. This abnormality may reflect a failure of cortical and/or cerebellar areas to coordinate saccadic and pursuit eye movements during visual tracking. The pharmacology of this phenomenon is not known. Here, we sought to replicate and extend the findings of Olincy et al (1998), who found that nicotine transiently reduced the number of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 75 publications
1
49
0
1
Order By: Relevance
“…For example several authors have linked increased antisaccade errors to dysfunctional working memory processes (Roberts et al, 1994, Hutton et al 20022004). Similarly intrusive anticipatory saccades that can occur during smooth pursuit eye movements have been argued to reflect a failure of inhibitory control mechanisms [Avila et al 2003]. Studies in patients with schizophrenia, who demonstrate both increased antisaccade errors and impaired smooth pursuit have found that nicotine can significantly ameliorate both of these deficits [Olincy et al, 2003;Larrison Briand and Sereno, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For example several authors have linked increased antisaccade errors to dysfunctional working memory processes (Roberts et al, 1994, Hutton et al 20022004). Similarly intrusive anticipatory saccades that can occur during smooth pursuit eye movements have been argued to reflect a failure of inhibitory control mechanisms [Avila et al 2003]. Studies in patients with schizophrenia, who demonstrate both increased antisaccade errors and impaired smooth pursuit have found that nicotine can significantly ameliorate both of these deficits [Olincy et al, 2003;Larrison Briand and Sereno, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Deficient P50 auditory sensory gating has been linked to polymorphisms at the site of the a7nAChR gene on chromosome 15q14 and is transiently reversed by nicotine administration in smokers with schizophrenia and in nonsmoking first-degree relatives of patients with schizophrenia (Adler et al, 1992(Adler et al, , 1993Freedman et al, 1997;Leonard et al, 2002). Nicotine also improves diseaseassociated deficits in prepulse inhibition (PPI) of the acoustic startle response (Kumari et al, 2001) and oculomotor function, with improvements reported in smooth pursuit eye movement (SPEM) and antisaccade error rates (Olincy et al, 1998(Olincy et al, , 2003Depatie et al, 2002;Sherr et al, 2002;Avila et al, 2003). These findings, combined with the observation that the prevalence of cigarette smoking is much higher in schizophrenia compared with the general population, (Hughes, 1986;de Leon et al, 2002) have led to the hypothesis that smoking represents a form of self-medication for patients with psychiatric illness, particularly schizophrenia (Glassman, 1993;Dalack et al, 1998;Kumari and Postma, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since brain KYNA levels are decreased 4 and 6 days after repeated nicotine administration, excessive smoking in the schizophrenic population could constitute an attempt to self-medicate (cf Introduction). Indeed, a reduction in brain KYNA enhances nicotinic and glutamatergic transmission (Alkondon et al, 2004) and could thus normalize gating (Adler et al, 1993) and eye-tracking Avila et al, 2003), deficit, and improve cognitive function (Mori and Mishina, 2003). However, the present data suggest that more prolonged exposure to nicotine may have the opposite, detrimental effects on sensory and cognitive modalities since brain KYNA levels are elevated (cf Shepard et al, 2003).…”
Section: Discussionmentioning
confidence: 62%